Behavior and Performance of Asphalt Concrete Modified by Crumb Rubber (International Journal of Innovative Research in Engineering & Management, 2022)
In our country, the increase in the  production of wastes has posed a great challenge for  humanity. India is the leading producer of waste rubber and  if any kind of method that makes it possible for us to reduce  the ill effects of it on the environment and human life is to  make use of it in the best possible way. Waste rubber, being  a non biodegradable material has found a better place in  case of embedding useful and effective properties in  bitumen thus enhancing the performance of bituminous  concrete. So researchers found its use in the case of bitumen  and in this paper we would be analyzing the performance  and behavior of bitumen modified with rubber. Some of the  main features of road pavement construction would be  studied; such features are: - stability, stiffness, fatigue,  resistance, rutting and so on.
Keywords: Stiffness; Crumb Rubber; Asphalt; Concrete; Pavement